Pengaruh Penggunaan Media Kolase berbahan Alam Terhadap Perkembangan Motorik Halus Anak Usia 5-6 Tahun di PAUD Telkom Ternate - Husen, Winda Nifia; Sahidun, Nurfitri (Jurnal Ilmiah Wahana Pendidikan, 2024)
The aim of this research is to find out whether there is an effect of using natural collage media on children's fine motor development. The formulation of the research problem is as follows: "Is there an effect of using collage media made from natural ingredients on children's fine motor development?". This type of research uses Quasi Experimental. In the population and sample of this study, students in group B1 as the control class and group B2 as the experimental class. The results of the study showed that N = 15 at a significance level of 0.05 (5%) with Df = n-2, then the r table value was 0.514. Which was carried out with the independent sample T test with the help of SPSS 20, it was obtained that the data from the test results were homogeneous, so that for hypothesis testing, the t-test can be used, namely the sample from the control class which has a value of 0.000 and the value of the experimental group t-test 0.000. which is a sign that there is a difference between the two groups. From this calculation, there is a Sig. (2-tailed) value of 0.000 in accordance with the decision making that if the Sig. (2-tailed) value is less than 0.05 (5%) in this case, it means that Ho is rejected and HI is accepted. Thus, the conclusion is that there is a significant influence on the development of fine motor skills of children in group B at PAUD Telkom Ternate